Equine nutrition and feeding - Frape, David , 1929- (Ames, Iowa : Wiley-Blackwell, 2010)
Equine Nutrition and Feeding is the seminal work on the subject. It covers all the key topics needed for equine nutrition degree course. This comprehensive and clearly evidenced textbook covers how food is digested and nutrients are used in growing, working and breeding horses
1. The digestive system -- 2. Utilization of the products of dietary energy and protein -- 3. The roles of major minerals and trace elements -- 4. Vitamin and water requirements -- 5. Ingredients of Horse feeds -- 6. Estimating nutrient requirements -- 7. Feeding the breeding mare, foal and stallion -- 8. Growth -- 9. Feeding for performance and the metabolism of during exercise -- 10. Grassland and pasture management -- 11. Pests and ailments related to grazing area, diet and housing -- 12. Laboratory methods for assessing nutritional status and some dietary options
Includes bibliographical references (p. 405-482) and indexes
Keywords: Horses -- Feeding and feeds; Horses -- Nutrition